2021
DOI: 10.3390/nu13051674
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Ramen: Investigating Methods to Improve Food Agency among College Students

Abstract: Many college students struggle to cook frequently, which has implications for their diet quality and health. Students’ ability to plan, procure, and prepare food (food agency) may be an important target for shifting the college student diet away from instant and inexpensive staples like packaged ramen. The randomized intervention study included two sequential cooking interventions: (1) six weeks of cooking classes based in food agency pedagogy held once per week, and (2) six weekly home delivered meal kits (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…While the current literature, including the results presented here, provides evidence that cooking interventions are effective in increasing confidence and skills (i.e., self-efficacy) around healthy meal preparation and consumption, associated changes in behavior have not been consistently demonstrated [ 18 , 19 , 20 ]. In a randomized and controlled trial evaluating the impact of a 6-week cooking skills intervention among university students in Brazil, improvements in self-efficacy, which were maintained at 6 months following the intervention, did not translate into more frequent home cooking postintervention or at follow up [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the current literature, including the results presented here, provides evidence that cooking interventions are effective in increasing confidence and skills (i.e., self-efficacy) around healthy meal preparation and consumption, associated changes in behavior have not been consistently demonstrated [ 18 , 19 , 20 ]. In a randomized and controlled trial evaluating the impact of a 6-week cooking skills intervention among university students in Brazil, improvements in self-efficacy, which were maintained at 6 months following the intervention, did not translate into more frequent home cooking postintervention or at follow up [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…Two systematic reviews, together covering studies through 2016, found that adults’ confidence and knowledge around healthy eating often increased after participation in cooking and nutrition interventions [ 16 , 17 ]. Since then, a small number of studies have evaluated the impact of cooking interventions including a teaching kitchen component in college students [ 12 , 18 , 19 , 20 ]. These studies observed increases in self-efficacy in cooking and fruit and vegetable consumption [ 12 , 18 ], nutrition or cooking knowledge [ 18 , 19 ], or Cooking and Food Provisioning Action Scale (CAFPAS) scores [ 20 ] among participants.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as few studies [ 39 , 40 ] have been published in the peer-reviewed literature assessing the associations between meal-kit use and nutritional outcomes, this analysis presents foundational estimates that future research can build on. Data from this analysis come from a nationally representative survey collected using online panels which have been shown to be a valid method for participant recruitment [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that although meal kits improved food agency, cooking classes designed to improve food agency were more effective. Additionally, meal kits did not have any significant effects on cooking frequency or diet quality [84]. Though meal kits are typically marketed towards higher-income households, there is evidence that meal kit interventions would be acceptable and highly utilized among families with low incomes.…”
Section: Meal Kitsmentioning
confidence: 93%